On‐Demand Control System for Deep Brain Stimulation for Treatment of Intention Tremor. Issue 3 (24th October 2012) - Yamamoto, Takamitsu; Katayama, Yoichi; Ushiba, Junichi; Yoshino, Hiroko; Obuchi, Toshiki; Kobayashi, Kazutaka; Oshima, Hideki; Fukaya, Chikashi
<x xml:space="preserve">Abstract</x> Objectives Intention tremor becomes evident only when patients intend to move their body and is characterized by dysmetria. We have developed an on‐demand control system that triggers the switching on/off of deep brain stimulation (DBS) instantly for the control of intention tremor. Material and Methods We used surface electrodes for the recording of electromyographic (EMG) activity, and the power of EMG activity was analyzed instantly employing the fast Fourier transform. The on‐demand control system switched on DBS when only the power of tremor frequency exceeded the on‐trigger threshold, and the system switched off DBS when the total power of EMG activity decreased below the off‐trigger threshold. Results The on‐demand control system triggered the switching on/off of DBS accurately, and controlled intention tremor completely. Our on‐demand control system is small and portable, and suitable for clinical use. Conclusions The on‐demand control system for DBS is useful for controlling intention tremor and may decrease the incidence of tolerance to DBS and may be a powerful tool for various applications of neuromodulation therapy.